A Comparison of Single and Combined Schemes of Asia-Pacific Colorectal Screening, Faecal Immunochemical and Stool Deoxyribonucleic Acid Testing for Community Colorectal Cancer Screening - Ze Y; Tu H; Zhang L; Bai Y; Ren Y; Chen X; Xue Y; Sun R; Yang Y; Yang J; Zhou X; Liu L (Journal of Multidisciplinary Healthcare, 2023)
Yuan Ze,1 Huiming Tu,2 Lin Zhang,3,4 Yu Bai,5 Yilin Ren,2 Xin Chen,1 Yuzheng Xue,2 Renjuan Sun,6 Yuling Yang,7 Jie Yang,2 Xuan Zhou,2 Li Liu8 1Wuxi School of Medicine, Jiangnan University, Wuxi, People’s Republic of China; 2Department of Gastroenterology, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 3Institute of Artificial Intelligence, Hefei Comprehensive National Science Center, Hefei, People’s Republic of China; 4School of Population Medicine and Public Health, Peking Union Medical College/Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 5Department of Gastroenterology, Changhai Hospital of Shanghai, Shanghai, People’s Republic of China; 6Outpatient Nursing department, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 7Nursing department of Geriatrics Ward, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 8Data Center, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of ChinaCorrespondence: Huiming Tu, Department of Gastroenterology, Affiliated Hospital of Jiangnan University, No. 1000, Hefeng Road, Binhu District, Wuxi, 214122, People’s Republic of China, Tel +86-13861753621, Email tuhuiming1891@163.comObjective: To compare the screening efficacy of colonoscopy and pathologically confirmed single and combined Asia-Pacific colorectal screening (APCS), faecal immunochemical testing (FIT) and stool deoxyribonucleic acid (sDNA) testing protocols.Methods: From April 2021 to April 2022, 842 volunteers participated in primary colorectal cancer (CRC) screenings using APCS scoring, FIT and sDNA testing and 115 underwent a colonoscopy. One hundred high-risk participants were then identified from the results of both processes. The differences in the three CRC screening tests in combination with the colonoscopy pathology diagnostics were evaluated using Cochran’s Q test, the Dunn–Bonferroni test and area under the receiver operating characteristic curve (AUC) value analysis.Results: Both FIT and sDNA testing demonstrated a 100% performance in detecting CRC. For advanced adenoma, the sensitivity of the FIT + sDNA test scheme (double positive) was 29.2%, and the sensitivities of the combined FIT + sDNA test and APCS scoring + sDNA test schemes were 62.5% and 95.8%, respectively. The FIT + sDNA testing kappa value of advanced colorectal neoplasia was 0.344 (p = 0.011). The sensitivity for nonadvanced adenoma of the APCS score + sDNA test scheme was 91.1%. In terms of positive results, the sensitivity of the APCS score + FIT + sDNA detection protocol was significantly higher than that of the APCS score, FIT, sDNA detection, and FIT + sDNA detection methods (adjusted p < 0.001, respectively). For the FIT + sDNA test, the kappa value was 0.220 (p = 0.015) and the AUC was 0.634 (p = 0.037). The specificity of the FIT + sDNA test scheme was 69.0%.Conclusion: The FIT + sDNA test scheme demonstrated superior diagnostic efficacy, and the combined APCS score + FIT + sDNA test scheme demonstrated remarkable improvements in CRC screening efficiency and sensitivity for detecting positive lesions.Keywords: faecal immunochemical testing, stool DNA test, colonoscopy, primary screening, colorectal cancer